Systematic Literature Review: Penggunaan Aplikasi Mathway terhadap Kemampuan Berpikir Kritis Siswa - Hikmah Fazariah; Yafizham Yafizham (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The ability to think critically is an important skill in the 21st century. The Mathway application offers various features that can help students learn mathematics. This research aims to systematically review the literature on the use of the Mathway application on students' critical thinking abilities. This research uses a literature review method by searching for relevant scientific articles in various databases such as Google Scholar, ScienceDirect, and ERIC. The research results show that using the Mathway application can help improve students' critical thinking skills. This is proven by several studies which show that students who use Mathway in their learning have higher scores on critical thinking ability tests compared to students who do not use Mathway.